Blockchain and electronic transactions in accounting - Shevchuk, Oleg; Muravskyi, Volodymyr (Herald of Economics, 2023)
Introduction. One of the most promising information and communication technologies in the digital economy is blockchain, which significantly changes the accounting and control of electronic transactions in business. Block-chain structuring of data is radically different from traditional methods of processing and storing accounting information, which determines the relevance of scientific research and practical developments in the field of using blockchain technology.The purpose of the article is to study the peculiarities of the implementation of electronic transactions in the conditions of using blockchain technology and the directions of transformation of accounting and control.Methods. Systemic, innovative, functional approaches and methods of generalization, bibliographic and comparative analysis were used in the process of realizing the established goal of scientific research.Results. The expediency of the transformation of the methodology and organization of accounting and control of electronic transactions under the influence of the use of blockchain technology is substantiated. The functional advantages of the blockchain network are defined: instant execution of electronic transactions, confidentiality of participants in electronic transactions, reliability of data storage, minimization of costs for the organization of information processing, significant variability of assets participating in electronic transactions, stability of functioning due to the impossibility of damaging or deleting databases, etc. The principles of blockchain technology, which are relevant for accounting and control of electronic transactions, have been formed: decentralization, transparency, accessibility, trust, cyber security, irreversibility, consensus, confidentiality. Eight main directions of transformation of accounting and control of electronic transactions in the blockchain network have been identified (positioning, variability, digitization, decentralization, protection and cyber security, monetary settlements, control, transformation of powers and regulations), the result of practical implementation of which is: automatic execution of accounting and control processes, prevention of accidental errors, prevention and elimination of cyber threats and fraudulent actions, minimization of enterprise costs; reduction of time for accounting and control procedures for operational management of enterprises, openness and publicity of accounting information about electronic business.Prospects. It is advisable to carry out further scientific research in the direction of: improving the legal regulation of electronic transactions; transformation of the organizational structure of the enterprise and the accounting and control unit; clarification of personnel job instructions and accounting policy of the enterprise.